Economics of land degradation in Eastern Africa - Oliver Kiptoo Kirui; Alisher Mirzabaev (University of Bonn, Center for Development Research (ZEF), 2014)
Land degradation remains a serious impediment to improving livelihoods in the Eastern Africa region. This working paper presents a general overview of the state and extent of land degradation in East Africa, explores its proximate and underlying drivers, identifies the land degradation hotspots in the region, and also discusses the productivity and poverty impacts of land degradation in the region. It is intended to serve as an exploratory tool for the ensuing more detailed quantitative analyses to support policy and investment programs to address land degradation in Eastern Africa. We critically review the strengths and weaknesses of the previous studies on the causes of land degradation in the region. Recent assessments show that land degradation affected 51%, 41%, 23%and 22% of land area in Tanzania, Malawi, Ethiopia and Kenya respectively. The key proximate causes leading to land degradation widely cited in the literature for the region include non-sustainable agricultural practices, overgrazing and overexploitation of forest and woodland resources, while the major underlying causes are believed to be population pressure, poverty and market and institutional failures. Water and wind erosion are the most widespread types of land degradation in the region. The economic damages from land degradation are substantial. To illustrate, this loss is estimated at about 3% of GDP in Ethiopia and about 9.5 - 11% of GDP in Malawi, annually. The available estimates indicate that yield reduction due to soil erosion may range from 2 - 40% depending on the crop and location across the Eastern Africa. In spite of these dynamics, the adoption of sustainable land management (SLM) practices in the Eastern Africa region, and in Sub-Saharan Africa, as a whole, is highly insufficient - just on about 3% of total cropland, according to some estimates. To address land degradation, there is a strong need to substantially increase the investments and strengthen the policy support for sustainable land management.
Keywords: 330; Economics of Land Degradation (ELD); Sustainable Land Management (SLM); Poverty; Eastern Africa